From decision to destination: factors influencing healthcare students’ career paths in Qatar - Yasin M. Yasin (14779381) (2024)
Healthcare education is crucial for building a workforce in Qatar that is in line with Vision 2030. Although various factors influence career choices, little research exists on their impact on healthcare students in Qatar. This study explores the factors influencing healthcare students in Qatar to pursue healthcare careers, as well as the facilitators and challenges they face during their education. A cross-sectional survey was conducted among 364 healthcare students in Qatar. Quantitative data was analyzed to identify key factors influencing career choice, while qualitative data provided deeper insights into challenges and support systems. Quantitative findings identified “contribution to society” and “quality” as key factors shaping career choices. Demographic variables such as gender, income, and birthplace influenced these decisions. Qualitative analysis revealed that students face numerous challenges, such as academic demands, financial pressures, and logistical difficulties, but these were mitigated by support from family, peers, and institutional resources. This study underscores the importance of tailored support systems to foster student retention and success in healthcare education, particularly for students from diverse cultural backgrounds. Policymakers and educators should develop strategies that support a sustainable, culturally competent healthcare workforce in Qatar that meets the nation’s evolving healthcare needs. Other Information Published in: BMC Medical Education License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1186/s12909-024-06527-3